Prevalence of sports participation among Brazilian adolescents: a systematic review - Santiago Maillane-Vanegas; Jamile Sanches Codogno; Bruna Camilo Turi; Diego Giuliano Destro Christofaro; Rômulo Araújo Fernandes (Universidade Federal de Santa Catarina, 2018)
The objective of this study was to describe the prevalence of sports participation in Brazilian children and adolescents using a systematic review approach. This review follows the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) statement and the protocol was previously registered on PROSPERO (95441), the searches were performed in the following electronic databases: PubMed, ScIELO, Bireme, and EMBASE. The search strategy included a combination of keywords: Children and adolescents, prevalence and sports participation. Four papers included 7104 adolescents aged from 10 to 18 years old, living in four different cities located at Southeast (n= 1) and South (n= 3) of Brazil data collections were carried out between 2004 and 2012. Most of the studies had cross-sectional design and the findings of all surveys were published in international journals. The definition of "sports participation" was not the same in all papers. The overall prevalence of sports participation among adolescents was 58.1%, higher among boys (65.9%) than in girls (51.5%). The systematic review identified that the prevalence of sports participation among Brazilian adolescents is low and significantly affected by gender.